Repositioning Titanium: An In Vitro Evaluation of Laser-Generated Microporous, Microrough Titanium Templates As a Potential Bridging Interface for Enhanced Osseointegration and Durability of Implants - Tang, Daniel; Yang, Liang-Yo; Ou, Keng-Liang; Oreffo, Richard O. C. (Frontiers in Bioengineering and Biotechnology, 2017)
Although titanium alloys remain the preferred biomaterials for the manufacture of biomedical implants today, such devices can fail within 15 years of implantation due to inadequate osseointegration. Furthermore, wear debris toxicity due to alloy metal ion release has been found to cause side-effects including neurotoxicity and chronic inflammation. Titanium, with its known biocompatibility, corrosion resistance, and high elastic modulus, could if harnessed in the form of a superficial scaffold or bridging device, resolve such issues. A novel three-dimensional culture approach was used to investigate the potential osteoinductive and osseointegrative capabilities of a laser-generated microporous, microrough medical grade IV titanium template on human skeletal stem cells. Human skeletal stem cells seeded on a rough 90 µm pore surface of ethylene oxide sterilized templates were observed to be strongly adherent, and to display early osteogenic differentiation, despite their inverted culture in basal conditions over 21 days. Limited cellular migration across the template surface highlighted the importance of high surface wettability in maximizing cell adhesion, spreading and cell-biomaterial interaction, while restricted cell ingrowth within the conical-shaped pores underlined the crucial role of pore geometry and size in determining the extent of osseointegration of an implant device. The overall findings indicate that titanium only devices, with appropriate optimizations to porosity and surface wettability, could yet play a major role in improving the long-term efficacy, durability, and safety of future implant technology.